KEBIJAKAN PEMERINTAH TENTANG SERTIFIKASI GURU MADRASAH - Arya Ficky Nugroho; Muhammad Syaifuddin; Asmuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article discusses the government policy on madrasah teacher certification as an effort to improve professionalism and the quality of Islamic education in Indonesia. This research employs a library study method with descriptive qualitative analysis of regulations, technical guidelines, and expert opinions. The findings show that certification plays an important role in standardizing teacher competence and increasing welfare through professional allowances. However, its implementation still faces challenges such as limited quotas, unequal access between public and private madrasahs, and digital administrative obstacles. This study recommends improving the implementation system and evaluating the certification impact to ensure the policy runs more effectively and equitably.